Discourse, gender, and violence: insights from news and social media texts - Maruenda-Bataller, Sergio; Mercé, Laura; Castellano-Ortolà, Elena (Linguistic insights, 2024)
"This book includes contributions to research in the area of language use and gender-based violence (GBV). It demonstrates how the mechanisms of gendered power in news and social media texts operate linguistically in the study of GBV. The collection offers both methodological insights from novel empirical studies and careful theorisations of discourse and gender-based violence"--